2021
DOI: 10.1039/d1sc04943g
|View full text |Cite
|
Sign up to set email alerts
|

Silicon – single molecule – silicon circuits

Abstract: Single-molecule circuits using silicon contacts are robust, conductive, controllable, and highly reproducible in blinking experiments, with enhanced conductance in break-junctions owing to residual dangling bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 103 publications
(155 reference statements)
0
13
1
Order By: Relevance
“…STM has proven to be an invaluable tool for studying conductive surfaces throughout the last four decades. The incursion of novel substrates and new deposition techniques helped to improve the capability to resolve structures at the atomic level, allowing the study of complex phenomena such as molecular bonding and hybridization states [ 121 ], in-situ chemical reactions for molecular engineering [ 122 ], or single-molecule junctions [ 123 ], to mention a few applications. These advances drive STM expansion in all directions and help conceptualize other instruments such as the AFM [ 124 ] or the scanning ion conductance microscope [ 125 ] that also allow the observation of biological samples.…”
Section: Perspectivementioning
confidence: 99%
“…STM has proven to be an invaluable tool for studying conductive surfaces throughout the last four decades. The incursion of novel substrates and new deposition techniques helped to improve the capability to resolve structures at the atomic level, allowing the study of complex phenomena such as molecular bonding and hybridization states [ 121 ], in-situ chemical reactions for molecular engineering [ 122 ], or single-molecule junctions [ 123 ], to mention a few applications. These advances drive STM expansion in all directions and help conceptualize other instruments such as the AFM [ 124 ] or the scanning ion conductance microscope [ 125 ] that also allow the observation of biological samples.…”
Section: Perspectivementioning
confidence: 99%
“…[35][36][37][38] Recently, it has been demonstrated that Si-H surfaces can spontaneously reduce the S-S bonds in disulde-terminated organic molecules and in the protein azurin that contains a peripheral S-S bond, enabling connecting these molecules to the Si surface via covalent S-Si bonds. [39][40][41] In this article, we use surface spectroscopy, electrochemical and single-molecule scanning tunnelling break junction techniques to (i) study the chemical reactivity of SARS-CoV-2 with surfaces of electrodes, (ii) electrically detect the spike protein and (iii) study the effect of electric elds on spike proteins at the single-molecule level (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…35–38 Recently, it has been demonstrated that Si–H surfaces can spontaneously reduce the S–S bonds in disulfide-terminated organic molecules and in the protein azurin that contains a peripheral S–S bond, enabling connecting these molecules to the Si surface via covalent S–Si bonds. 39–41…”
Section: Introductionmentioning
confidence: 99%
“…The energy band regulation has been effectively realized in single-molecule PN junctions. Similar models of P­(N)–molecule–P­(N) junctions with P­(N)-doped semiconductor electrodes, by adjusting the molecule/electrode interface, can realize special heterojunction functions. The design of the molecule itself can provide more possibilities for adjusting the inherent electrical properties of single-molecule heterojunctions.…”
Section: Introductionmentioning
confidence: 99%